A Comparison of 111In-Labelled Polymer Beads and 99mTc-Sn-Colloid as Solid Food and Semi-Solid Food Tracers for Scintigraphic Gastric Emptying Studies - Irene, C. Dormehl; Maryke, du Plessis; Marianna, Maree; Pilloy, W. J. (Nuklearmedizin - NuclearMedicine, 1986)
In order to establish the efficacy of labelling a solid meal and a semi-solid meal with either 111ln-labelled polymer beads or 99mTc-tin colloid beagle dogs were fed variously labelled meals of different consistencies and then monitored by scintigraphy for gastric motility patterns. The labelling with each tracer was either performed by thoroughly mixing it into the food before cooking, or alternatively by surface labelling after the food had been cooked. For the 99mTc-Sn- colloid tracer no difference was found in the measured gastric emptying times resulting from either pre-cooking labelling or surface labelling of the meals. Cooking the tracer together with the ingredients does however seem to promote a firm entrapment of the 111ln-polymer beads into a solid protein, and in this manner the111In-labelled resin appears to be a reliable solid food tracer. Surface labelling with 111ln-polymer beads of a solid meal with a smooth texture fails totally and the tracer empties with the liquid phase.